Persepsi Dan Minat Mahasiswa Jurusan Akuntansi Fakultas Ekonomi Terhadap Profesi Akuntan Publik ( Studi kasus pada Universitas Muhammadiyah Surakarta dan Universitas Sebelas Maret Surakarta ) - Fitria, Nur; , Dr. Fatchan Achyani, M.Si (2016)
The purpose of this study was to explore the perceptions and interests of students majoring in Accounting Faculty of Economics, Muhammadiyah University of Surakarta and March Surakarta to the public accounting profession. This study was conducted by surveying directly on the object of researchers that all students majoring in Accounting Faculty of Economics, Muhammadiyah University of Surakarta (UMS) and March University of Surakarta (UNS) class of 2011 through 2013, both regular programs as well as non-regular with the provisions already follow the course of auditing. The analytical method used is multiple linear regression, and convenience sampling is for sampling methods. From the data obtained during the survey will obtain a clear picture that will allow researchers to determine the perceptions and interests of students majoring in Accounting Faculty of Economics of the public accounting profession. The results of this analysis showed that the public accounting profession in the eyes of students majoring in Accounting Faculty of Economics is a respected profession and the public accounting profession is seen as promising. The results showed that students' perceptions variable accounting department Faculty of Economics and significant positive effect on the variable public accounting profession with tvalue (5861) > ttable (1.985) p value < 0.05 ; and interest in the accounting profession and significant positive effect on the variable with the public accounting profession tcount (3.350) > t table (1.985) p value < 0.05 . There is a simultaneous influence between variable perception and interests of students majoring in Accounting Faculty of Economics of the public accounting profession with Fhitung (36.251) > F table (3.090 ) with p value < 0.05. R2 test results obtained 41.6 %, meaning that changes in the public accounting profession is because of the variation of the variable perception and interests of students majoring in Accounting Faculty of Economics .